Smart House Development Based On Microcontroller AVR-ATMEGA328 - . Haryansyah; Fitriansyah Ahmad; . Hadriansa (Bandar Lampung University (UBL), 2012)
Microcontroller as a device that capable to managing the data and process, there was integrated RAM and ROM on the chip, that mean this device is a low-speed mini computer. Prices are relatively affordable and easily available in everywhereisaseparateeasytostart using itineveryday life.Smarthousedevelopment inthis research is a form of applied use ofthe microcontroller is able to control the device in the house remotelyanddirectly. Controlactivity of lights, doors, windowsandother devices (that must be converted into electric device) in the house that are likely tobe controlled by the owner of the house with this device.Remote access into thesmart homeis being carried outby connecting themicrocontrollerwithethernetmodule, which can beaccessed globaly using the Internet mediaand the computer network in locally.Whileaccessmanually, building the centralset-top-box modulewith theimplementation ofa miniLCDscreenthat integrate into the microcontroller using digital menus approaches that can bedirectly accessedby the ownertoproperly managed. Otherdevices module will beintegratedin themicrocontroller. ThereisaRTC(Real TimeClock) module to reference the time for action of the application.The final results of his study is the house that is able to govern themselves with thehelp ofa microcontrollerthat can be think themselves. Withbroadly accesscanuse theInternetmedia, then the housewill be increasinglycontrolledbybothlong-distance.